2005
DOI: 10.1080/00958970512331327401
|View full text |Cite
|
Sign up to set email alerts
|

Ligand field strengths of carbon monoxide and cyanide in octahedral coordination

Abstract: Ligand field splittings were extracted from absorption spectra of metal hexacarbonyl and hexacyano complexes over 35 years ago by Gray and coworkers (J. Am. Chem. Soc., 85, 2922Soc., 85, (1963 ibid. 90, 4260, 5713 (1968)). Recent time-dependent density functional theory calculations by Baerends and coworkers (J. Am. Chem. Soc., 121, 10356 (1999)) on M(CO) 6 with M ¼ Cr, Mo, W raised questions about the magnitudes of these ligand field splittings. In order to reexamine such effects systematically, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
20
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 17 publications
6
20
0
3
Order By: Relevance
“…These values are in the same range as those predicted by calculations reported both here and elsewhere. 16,17,27,29,30 They also agree well with the more qualitative results of other experimental techniques, including …”
Section: Discussionsupporting
confidence: 86%
“…These values are in the same range as those predicted by calculations reported both here and elsewhere. 16,17,27,29,30 They also agree well with the more qualitative results of other experimental techniques, including …”
Section: Discussionsupporting
confidence: 86%
“…This is due to the strong π-acceptor nature of the CO ligand. Also note that the CO ligand is charge-free whereas the cyanide carries a negative charge, and this could partially hinder the charge transfer to the ligand sites45. We conclude this section by noting that the strength of back bonding decreases in the following order of metal complexes: Fe(CO) 5  > [Fe(CN) 6 ] 4−  > [Co(CN) 6 ] 3− .…”
Section: Discussionmentioning
confidence: 85%
“…[9] More recently, Scheidt et al reported a complex containing five-coordinate iron that strongly demonstrates the weaker-field nature of cyanide. [10] The complex in question is [K(222)][Fe(tpp)(CN)], which is the first monocyano complex of an iron(II) porphyrin.…”
mentioning
confidence: 98%
“…Prior to this work, some calculations on the ligand field strengths of strong-field ligands had been reported. [8,9] Scheme 1. The spectrochemical series developed by Tsuchida.…”
mentioning
confidence: 99%